Hubungan Financial Stress dengan Student Economic Behavior pada Mahasiswa - Mutiara Sahra Fadhilah Nofitri Yati; Halimah Halimah; Lucky Purwantini (Universitas Palangka Raya, 2026)
This study aimed to examine the relationship between financial stress and students' economic behavior and to identify differences in both variables based on demographic characteristics. This research employed a quantitative approach with a correlational design. The participants were 1,062 undergraduate students from various universities in Indonesia selected through purposive sampling. Data were collected using the Financial Stress Scale for Undergraduate Students and the Students' Economic Behavior Scale. Data were analyzed using Spearman Rank Correlation, Mann-Whitney U Test, and Kruskal-Wallis Test. The results indicated that there was no significant relationship between financial stress and students' economic behavior (r = -0.014; p = 0.655). In addition, no significant differences were found in financial stress or students' economic behavior based on gender, scholarship status, or migration status. However, significant differences in financial stress were found based on living arrangements, while students' economic behavior differed significantly based on parents' income. This study concludes that financial stress is not significantly associated with students' economic behavior, although several demographic characteristics differentiate each variable.